The Peruvian experiment reconsidered - McClintock, Cynthia; Lowenthal, Abraham F. (Princeton legacy library., 1983)
Peru's self-proclaimed "revolution"-surprisingly extensive reforms initiated by the military government-has aroused great interest all over Latin America and the Third World. This book is the first systematic and comprehensive attempt to appraise Peru's current experiment in both national and regional perspective. It compares recent innovative approaches to Peru's problems with the methods used by earlier regimes, providing original and stimulating interpretations of contemporary Peru from the viewpoints of political science, sociology, history, economics, and education. Among the issues considered are the military regime's policies regarding income distribution, foreign investment, education, urbanization, worker-management relations, and land reform.Contributors: Abraham F. Lowenthal, Julio Cotler, Richard Webb, David Collier, Susan Bourque and Scott Palmer, Colin Harding, Robert Drysdale and Robert Myers, Shane Hunt, Peter T. Knight, Jane Jaquette.Originally published in 1976.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.